Analysis of Gold Concentration and Leaching Efficiency of PCB Waste Using Atomic Absorption Spectroscopy - Maulina Wulansari; Yus Rama Denny M; Devi Ayu Nur’aini; Mohammad Nouvaldy (IAIN Sorong, 2026)
Printed circuit board (PCB) waste is a source of valuable metals with high potential for recycling, primarily because it contains relatively high concentrations of gold. This study aims to analyze the gold concentration in the filtrate obtained from leaching PCB waste using atomic absorption spectroscopy (AAS) and to evaluate the leaching efficiency achieved. The study began with sample characterization using Fire Assay and ICP-OES, followed by a pre-leaching process using 65% HNO₃ at 70°C for 60 minutes. The pre-leaching residue was then subjected to leaching using a mixture of 37% HCl and 65% HNO₃ in a 1:3 ratio at 70°C for 90 minutes. The leaching filtrate was analyzed using AAS after dilution: 1 mL of the solution was taken and diluted to 25 mL. The initial characterization results showed that the PCB sample contained 522 ppm of gold from 303.20 grams of PCB sample. AAS analysis revealed a gold concentration of 1.307 ppm in the diluted solution, equivalent to 81,69 ppm in the actual filtrate, with a leaching recovery rate of 34,44%. These results indicate that the leaching process was able to dissolve gold from the PCB matrix into the liquid phase. This study provides preliminary information on the potential for utilizing PCB waste as a source of secondary precious metals through hydrometallurgical methods and can serve as a basis for further research on leaching process optimization and gold recovery.